The Faces of Reason : An Essay on Philosophy and Culture in English Canada1850-1950 - Armour, Leslie (Book collections on Project MUSE., 2006)
The Faces of Reason traces the history of philosophy in English Canada from 1850 to 1950, examining the major English-Canadian philosophers in detail adn setting them in the context of the main currents of Canadian thought. The book concludes with a brief survey of the period after 1950. What is distinctive in Canadian philosophy, say the authors, is the concept of reason and the uses to which it is put. Reason has interacted with experience in a new world and a cold climate to create a distinctive Canadian community. The diversity of political, geographic, social, and religious factors has.